APLIKASI MUSYARAKAH MUTANAQISAH DALAM PEMBIAYAAN MIKRO KEWANGAN ISLAM: Application of Musharakah Mutanaqisah in Islamic Microfinancing - Samsudin, Zuhaira; Ab Ghani, Ab Mumin (Jurnal Syariah, 2015)
Islamic microfinance has become an important part of the financial system, recognized locally and internationally, as a significant solution in addressing the problems of poverty. However, most of the financial institutions are reluctant to use the form of equity financing especially to micro entrepreneurs, because they have a negative perception of the entrepreneurs. They are often regarded as risk borrowers, having lack of experience and skills and therefore not being viable. However, the author believes that equity financing is an alternative for the entrepreneurs to overcome their financial problems as well as issues of management skills. Theoretical studies have been conducted to examine musharakah mutanaqisah instrument and the results show that musharakah mutanaqisah financing can be one of the most potential instrument for micro entrepreneurs. The main aspects to note are those of the partnership as well as the mechanism of the pricing of the unit and ijarah rental. Purchase of shares in units make this instrument more practical and flexible to implement. This paper will elaborate on musharakah mutanaqisah contract generally and its application in Islamic microfinance through the mechanism of purchasing units.